HIV Enteropathy in an Adolescent Bangladeshi Girl: A Case Report (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
We report a case of 14 years old girl who presented with intractable diarrhoea, low-grade irregular fever, multiplepainful oral ulcers, recurrent boils over different parts of the body for 1 year, and weight loss for 6 months. Previouslyshe was erroneously diagnosed as intestinal tuberculosis. The patient did not respond to antitubercular drugs. She alsogot prednisolone and mesalamine as the treatment of inflammatory bowel disease. Now she is diagnosed as a case ofAIDS-stage 3. We describe the case and discuss its clinical and biochemical findings with treatment.Bangabandhu Sheikh Mujib Med. Coll. J. 2022;1(1):49-52